2012
DOI: 10.3382/ps.2011-02031
|View full text |Cite
|
Sign up to set email alerts
|

Effect of iodine-enriched yeast supplementation of diet on performance of laying hens, egg traits, and egg iodine content

Abstract: The aim of the study was to evaluate the effect of iodine yeast (I-yeast) supplementation on the performance, egg traits, and iodine content of eggs of laying hens. The experiment was conducted as a completely randomized design. A total of 60 laying hens (Hy-Line Brown), 25 wk of age, was divided into 3 groups (4 replicates), and a feeding experiment was conducted for 12 wk. The concentrations and forms of iodine added to the basal diet were as follows: control group, 1 mg of iodine/kg of feed, Ca(IO(3))(2)•H(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 26 publications
1
21
2
1
Order By: Relevance
“…In agreement with the present study, some researchers reported that I supplementation to layer hens diets had no significant effects on egg production, egg mass production, egg weight, feed intake, FCR, un‐normal eggs and body weight changes (Lichovnikova & Zeman, ; Opaliński et al., ; Yalçin, Kahraman, Yalcin, Yalcin, & Dedeoglu, ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with the present study, some researchers reported that I supplementation to layer hens diets had no significant effects on egg production, egg mass production, egg weight, feed intake, FCR, un‐normal eggs and body weight changes (Lichovnikova & Zeman, ; Opaliński et al., ; Yalçin, Kahraman, Yalcin, Yalcin, & Dedeoglu, ).…”
Section: Discussionsupporting
confidence: 92%
“…Opaliński et al. () used Hy‐Line Brown laying hen during a 12‐week period and reported that dietary I supplementation significantly improves the egg yolk colour ( p = .002). Yalçin et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a lower weight of eggshell (7.00 g) in iodine eggs was recorded in comparison with the control group (p<0.05). This response was similar with the findings of the study conducted by Lichovnikova et al (2003) with long-term effects using higher amount of iodine, but in opposition to findings reported by Lichovnikova and Zeman (2004) and Opalinski et al (2012).…”
Section: Results and Disscusioncontrasting
confidence: 44%
“…Enrichment of egg content with some supplements was performed with modification of the feed composition (Gjorgovska and Filev, 2011). The most common enriched eggs are with omega Opalinski et al, 2012). A lot of studies presented the content of the supplementary element in the eggs enriched as functional food, but there is a lack of information about the egg structure parameters and productive performance.…”
Section: Introductionmentioning
confidence: 99%
“…Opaliński et al [20] showed that the use of yeast enriched with iodine in laying hens significantly increases the level of this element in the egg. In these studies, the birds were divided into three groups.…”
Section: Enrichment Of Eggs Withmentioning
confidence: 99%